Implementation of the Problem Based Learning (PBL) Model in Science Learning on the Material of Changes in the State of Objects in MI/SD - Rista Chamelia; Rosyidiana, Hafidz (Jurnal Multidisiplin Indonesia, 2025)
This article discusses the implementation of the Problem Based Learning (PBL) model in science learning, specifically on the topic of changes in the states of matter in elementary schools. PBL is a student centered learning model that presents learners with real-world problems to be analyzed and solved through discussion, investigation, and the presentation of results. The topic of changes in the states of matter is highly relevant to be taught using PBL because it can be easily observed in daily life, such as melting, freezing, evaporating, condensing, and sublimating. The implementation of PBL has been proven to enhance students' activeness, conceptual understanding, critical thinking skills, and collaborative abilities. This article describes the concept of PBL, steps for its implementation, examples of learning activities, and the benefits and challenges of applying it in science instruction.